2006
DOI: 10.1037/0022-0167.53.3.338
|View full text |Cite
|
Sign up to set email alerts
|

Differential social comparison processes in women with and without eating disorder symptoms.

Abstract: On the basis of predictions from social comparison theory (L. Festinger, 1954) and informed by findings from the social comparison and eating disorder literatures, hypotheses were tested regarding the social comparison behaviors of women with eating disorder symptoms and their asymptomatic peers. Results indicated differentiating social-cognitive processes for these groups. First, a greater tendency to engage in everyday social comparison predicted the presence of eating disorder symptoms. Second, social compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 99 publications
9
81
0
Order By: Relevance
“…indicate that, in general, body image and eating disturbances are associated with elevated social comparison levels, 45,46 and people with AN have been shown to display more unfavourable social comparisons than those without eating disorders. 20 Based on these findings and in line with Festinger's social comparison theory, 47 participants with AN may have judged themselves as being inferior to the other woman in terms of appearance, leading to an enhanced degree of body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…indicate that, in general, body image and eating disturbances are associated with elevated social comparison levels, 45,46 and people with AN have been shown to display more unfavourable social comparisons than those without eating disorders. 20 Based on these findings and in line with Festinger's social comparison theory, 47 participants with AN may have judged themselves as being inferior to the other woman in terms of appearance, leading to an enhanced degree of body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The theory states that "humans have a drive to assess how they are doing and in order to assess how they are doing, they seek standards against which to compare themselves. When objective standards are not available, people look to their social environments and engage in comparison with available others" (Corning et al, 2006). Social comparison theory has been applied to various research areas that may explain why people are motivated to engage in healthpromoting or health damaging behaviors (Festinger, 1954).…”
Section: Introductionmentioning
confidence: 99%
“…Austin (2000) reported that 10-15 % of girls and young women who are tested in studies actually score above the cut-off point for probable disordered eating. Moreover, up to 59 % of college women endorse skipping meals to control their weight (Tylka et al 2002), and between 34 and 67 % of college women may engage in such behaviors to the point that they would meet criteria for a ''subclinical'' eating disorder (Corning et al 2006).…”
Section: Introductionmentioning
confidence: 99%